Finding Hazardous Asteroids Using Infrared and Visible Wavelength Telescopes - Melosh, Jay; Harris, Alan; Ida, Bhavya Lal; McFadden, Lucy; Mommert, Michael; Rieke, George; Rivkin, Andrew; Scheeres, Daniel; Tedesco, E. F. (The National Academies Press, 2019)
In summer 2018, NASA’s chief scientist asked the National Academies of Sciences, Engineering, and Medicine to establish a study to address the issue of the relative advantages and disadvantages of infrared and visible observations of near Earth objects (NEOs). NASA has had an NEO observation program for nearly two decades using ground-based telescopes to search the night sky for NEOs that are large enough to cause major damage if they impact Earth. Since 2005, NASA has been guided in its search by the requirements of the George E. Brown, Jr. Near-Earth Object Survey Act. In recent years, NASA has used a space-based telescope to aid in its NEO search and has studied the possibility of using a dedicated space-based telescope to continue this work. This report of the Committee on Near Earth Object Observations in the Infrared and Visible Wavelengths addresses the space-based telescope subject while acknowledging that there are many larger issues associated with detecting, tracking, and characterizing NEOs. In December 2018, an asteroid exploded in the upper atmosphere over the Bering Sea (western Pacific Ocean) with an explosive force initially estimated to be nearly 200 kilotons, or over 10 times that of the Hiroshima bomb. This event, which was detected by various sensors and spotted by a Japanese weather satellite, demonstrates that Earth is frequently hit by objects, some of which could cause significant damage if they hit a populated area, as happened almost 6 years earlier over the Russian city of Chelyabinsk. Currently, NASA funds a network of ground-based telescopes and a single, soon-to-expire space-based asset to detect and track large asteroids that could cause major damage if they struck Earth. In 2018, the National Academies of Sciences, Engineering, and Medicine established the ad hoc Committee on Near Earth Object Observations in the Infrared and Visible Wavelengths to investigate and make recommendations about a space-based telescope’s capabilities, focusing on the following tasks: - Explore the ...